The rancher's promise - Harlen, Brenda (Harlen, Brenda. Match made in Haven., 2021)
Rancher Mitchell Gilmore has always loved the now-widowed Lindsay Delgado and now he is ready to risk their lifelong friendship to build a family and a future together.